ANALYSIS OF THE IMPLEMENTATION OF STANDARD FORM CONTRACTS ACCORDING TO ISLAMIC LAW (STUDY ON BANK SYARIAH MANDIRI) - Jalilah Jalilah; Nurul Hijri (SHIBGHAH: Journal of Muslim Societies, 2019)
This study seeks to analyze the application of standard form contracts imposed on bankssharia. The existence of a standard form contract in professional interactions of sharia business has indeed caused pros and cons in society, especially among legal experts, although it could facilitate and save time, it is also against the sharia principle of wronging others. This research aims to find out how the practice of applying and reviewing Islamic law is implemented intostandard form contracts on musyarakah financing in BSM Banda Aceh branch, including the positive and negative sides from the application of the standard form contract. The research method used is the qualitative method through primary data obtained from the field. The results showed that the standard contract at musyarakah financing at BSM Banda Aceh Branch is final and cannot be revised by the customers. Making contracts without involving the customers and the room of negotiation causes that this standard form contract is contrary to the principle of contracting in Islam, namely the principal freedom of contract, the principle of benefit (not burdensome) and the principle of balance (justice). Nonetheless, the standard contract on musyarakah financing is legally valid because the fulfillment of the terms of harmony and the terms of contract in Islam are indicated by the signing of the standard contract by both parties as proof that both parties are equally pleased. The existence of a standard contract on musyarakah financing has a positive side, and negatives are comparable, because, on the one hand, it makes it easy and saves time, on the other hand, incriminating next party. Therefore, it is deemed necessary to negotiate or eliminate a clause which is burdensome to create a balanced, fair and mutual cooperation contract between the two parties.